Estimating Rooftop Solar Potential in Urban Environments: A Generalized Approach and Assessment of the Galápagos Islands - Tian, Amy; Zünd, Daniel; Bettencourt, Luís M. A. (Frontiers in Sustainable Cities, 2021)
Presently, many island communities are largely dependent on fossil fuel resources for energy, leaving the abundance of renewable energy resources largely untapped. Although various solar energy potential modeling tools have been developed, most require high-resolution data, which do not presently exist for many developing countries or remote areas. Here, we calculate the potential of rooftop solar systems using low-cost, readily obtainable data and methods. This approach can be replicated by local communities and decision-makers to obtain an estimate of solar potential before investing in more detailed analysis. We illustrate the use of these methods on the two major urban centers on the Galápagos Islands (Ecuador), Puerto Baquerizo Moreno and Puerto Ayora. Our results show that a minimum of 21% and 27% of the total rooftop area must be covered with today's solar energy production technology to meet the current electricity demand of Puerto Baquerizo Moreno and Puerto Ayora, respectively. Additionally, the results demonstrate that Puerto Baquerizo Moreno has a higher production potential than Puerto Ayora, making it an attractive option for solar development that does not compete with the scarce land resources, most of which must be preserved as natural protected areas.